Diagnóstico situacional e proposta para a implementação do Sistema Nacional de Segurança Alimentar e Nutricional em São Cristóvão, Sergipe - Santos, Adriana Correia dos (2018)
This study aims to diagnose the situation of SAN in the city of São Cristóvão, Sergipe, and propose the implementation of the Food and Nutrition Security System. A cross-sectional, observational study with qualitative and quantitative research techniques was carried out. The research was carried out in two phases. The first phase consisted in the accomplishment of the situational diagnosis of the municipality based on the collection of primary and secondary data. For the secondary data, information was collected on socioeconomic and demographic indicators of the municipality, as well as the indicators related to the SAN issue. The primary data were obtained through a structured form with the municipal managers on existing programs and actions in São Cristóvão, a survey of the components necessary for the implementation of SISAN. Recorded interviews were carried out mediated by a semi-structured script with the municipal managers and municipal councilors of SAN of São Cristóvão to identify the perception about SAN, SISAN and potentialities and difficulties existent for the operationalization of the actions and programs of Nutritional Food Security. The second phase consisted of the elaboration of recommendations for the implementation of SISAN in the municipality based on the situational diagnosis. The analysis of qualitative data was performed through content analysis. For the quantitative analyzes, descriptive statistics (frequency, measures of central tendency and dispersion) were used according to the nature of each variable of the study. There were 3 managers and 12 advisers. The municipality presented an important economic and population growth. SAN indicators revealed that food production is focused on monoculture, access to the general sewage network by the population is precarious, there is a high prevalence of malnutrition and overweight in its population, as well as a high income, unemployment and income discrepancy. poverty. The municipality mainly presents assistance programs and actions and specific actions for the generation of income and strengthening of family agriculture. Of the components required for membership in SISAN there is the established and active SAN Council. The perception of managers and advisors about SAN and SISAN is limited. The main factors that facilitate the implementation of SAN actions and programs reported by the municipal managers were the articulation between the secretariats, the management commitment, and the main difficulties were the limited knowledge of the secretariats and population on the subject, reduced staff, lack of social participation and diagnosis. It is noticed the need to create public policies and actions aimed at guaranteeing the SAN of the population with the incorporation of intersectoriality in all stages of the cycle.